TASTE LEVEL OF FISH DRUMSTICK “DRAGON FEET” MADE FROM LARGE PELAGIC FISH MEAT - Junianto, Junianto; Gunawan, Nesya Putri; Damayanti, Yohana; Wijayanto, Rahmat (AQUASAINS, 2024)
The vast potential of Indonesia's seas makes fish a vital food source, contributing significantly to food availability in the country. Among the commonly caught species are large pelagic fish, such as tuna, skipjack tuna, and mackerel. To diversify processed fish products, large pelagic fish are transformed into innovative products, including "dragon's foot" products. This research aimed to identify the most suitable type of large pelagic fish meat for producing the most preferred dragon's foot product. The study employed an experimental method with three treatments based on the type of fish meat used: tuna, mackerel, and skipjack. The resulting dragon's foot products were evaluated for appearance, aroma, texture, and taste preferences by 15 semi-trained panelists. Statistical analysis was performed using the non-parametric Friedman test and paired comparison test, while the Bayes method was applied to determine the optimal treatment. The results revealed that the meat of large pelagic fish—specifically tuna, mackerel, and skipjack—serves as the primary ingredient in making dragon's foot products. Among these, the dragon's foot products made from tuna meat were the most favored by the panelists.Keywords: Bayes method, non-parametric analysis, product preference, sensory evaluation.